2007
DOI: 10.15666/aeer/0502_025036
|View full text |Cite
|
Sign up to set email alerts
|

Pits Conserve Species Diversity in an Overgrazed Grassland

Abstract: Abstract. Decrease in species diversity by overgrazing is one of the crucial indicators for ecosystem deterioration. Sika deer (Cervus nippon Tamminck) has grazed various plants on Nakajima Island, Hokkaido, Japan, for a few decades, due to low food availability. We examined if diverse microtopography supported high species diversity by conserving specific plants on the grassland of the island where overgrazing by deer occurred. Based on TWINSPAN analysis, three plant community types were classified: grassland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Other studies agree with our results, indicating the genus Oxalis as an unpalatable plant (Reimoser et al 1999) and including the genus Cardamine among common species germinating from dung (Gill & Beardall 2001;Pakeman et al 2002). In addition, several studies found both genera more frequent in grazed areas than in fenced areas: for Oxalis see McEvoy et al (2006) and Tsuyuzaki and Takahashi (2007); for Cardamine see Webster et al (2005). So although the plant community results showed that tall species increased in fenced areas, the cover of M. struthiopteris indicated that this fern is very competitive when not subject to grazing.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies agree with our results, indicating the genus Oxalis as an unpalatable plant (Reimoser et al 1999) and including the genus Cardamine among common species germinating from dung (Gill & Beardall 2001;Pakeman et al 2002). In addition, several studies found both genera more frequent in grazed areas than in fenced areas: for Oxalis see McEvoy et al (2006) and Tsuyuzaki and Takahashi (2007); for Cardamine see Webster et al (2005). So although the plant community results showed that tall species increased in fenced areas, the cover of M. struthiopteris indicated that this fern is very competitive when not subject to grazing.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, several studies found both genera more frequent in grazed areas than in fenced areas: for Oxalis see McEvoy et al . () and Tsuyuzaki and Takahashi (); for Cardamine see Webster et al . ().…”
Section: Discussionmentioning
confidence: 99%
“…The analyses done in relation to topographic factors and their relationships with ecological groups can be concluded that the aspect was the important variable among topographic factors in this study. Tsuyuzaki and Takhashi (2007) stated that topography and it's relationship with environmental factors such as light and soil moisture is the most important factor in determining the structure of plant communities and also, is a necessary condition for maintaining high diversity of rare species in degraded areas of Hokkaido in Japan. Also, the topographic factors were introduced as an important factor in distribution of alpine vegetation in the mountains of New Zealand (Mark et al 2000).…”
Section: Discussionmentioning
confidence: 99%